Density-Based Characterization of Microplastics via Cross-Halbach Magnetic Levitation - Chenxin Lyu; Chengqian Zhang; Baocai Zhang; Xuebin Ni; Hongchao Wang; Peng Zhao (Nanomaterials)
The analysis of microplastics poses significant challenges for conventional characterization techniques due to their small size and low concentrations. Magnetic levitation (MagLev), already proven effective for microscale material testing, provides a robust solution for sensitive, accessible, and untethered characterization of such materials. In this paper, we propose a Cross-Halbach magnetic levitation device to measure the densities of microscale plastic materials. Common types of plastic samples, varying in size and concentration, are successfully levitated, and the levitation times are recorded. The samples of common microplastic materials are characterized in less than 180 s. The characterized density values are validated against theoretical results, enabling density-based identification of microplastics. The experimental results demonstrate that the magnetic levitation method is suitable for the characterization of small-sized plastic materials, and the high-speed, low-volume measurement of plastic samples lays the foundation for future applications such as detection, separation, and recycling of ultrafine materials.